Toward a Live(d) Black World for Black Children / Amari Johnson’s Under a Black Star: The Maroon Impulse in New Orleans - Craig, John Pierre (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
This review of Amari Johnson’s Under a Black Star examines his autoethnographic account of the BlackStar community in New Orleans in the wake of Hurricane Katrina. Johnson reframes marronage away from overdetermined focus on escape and instead as pursuit of freedom, a process of disengagement, flight, and reengagement. I analyze the central concepts in the book and how they articulate a desire-based pedagogy. Following Johnson’s lead, I situate this work within Black geographies to think through how these practices create safety and possibility for Black children while also raising critical questions about making a live(d) Black world on Indigenous lands.